2022
DOI: 10.4103/jfmpc.jfmpc_165_22
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of isolated systolic and isolated diastolic hypertension in India: Insights from the national family health survey (NFHS)- 4

Abstract: Background: Isolated Systolic Hypertension (ISH) and Isolated Diastolic Hypertension (IDH) are often the ignored forms of hypertension and are determinants of future cardiac and neurological events and contribute to mortality. However, the nationally representative estimates of both these forms of hypertension remain unknown from India. Aim: To estimate the ISH and IDH from a nationally representative survey of India. Material and Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…215 According to the National Family Health Survey (NFHS), the prevalence of ISH and IDH in India was found to be 1.2% and 5.7%, respectively. 216 Another study reported a prevalence of 4.3% (5.1% in men and 3.6% in women). 217 Asian populations are at a heightened risk of systolic hypertension compared to Western populations, which amplifies the susceptibility to cardiovascular disorders, declining renal function, and mortality.…”
Section: Hypertension In Elderlymentioning
confidence: 97%
“…215 According to the National Family Health Survey (NFHS), the prevalence of ISH and IDH in India was found to be 1.2% and 5.7%, respectively. 216 Another study reported a prevalence of 4.3% (5.1% in men and 3.6% in women). 217 Asian populations are at a heightened risk of systolic hypertension compared to Western populations, which amplifies the susceptibility to cardiovascular disorders, declining renal function, and mortality.…”
Section: Hypertension In Elderlymentioning
confidence: 97%